The Impact of Social Network Marketing on University Students' Purchase Intention and How It Is Affected of Consumer Engagement - Hartiwi Prabowo; Rini Kurnia Sari; Stephanie Bangapadang (IJNMT (International Journal of New Media Technology), 2019)
The research conducted is to know the impact of social network marketing on consumer purchase intention and consumers who become research are active students at private universities in Jakarta, and how social network marketing also affect consumer engagement (as moderate variable). The research method used in this research is quantitative research method. A method of data collection used in this research is a questionnaire distributed to 119 university students. The results of this study showed that social network marketing has a strong and significant impact oncustomer engagement, customer engagementhas a strong and significant impact on consumer purchase intention, social network marketing has a strong and significant impact consumer purchase intention, and also there is a significant impact from social network marketing on consumer purchase intention through consumer engagement.